O latenira Iny: pássaros e plumária no rio Araguaia - Yabagata, Lucas Veloso (2023)
The work is dedicated to outlining reflections on the relationships established between the Iny, a people who have inhabited the banks of the Araguaia River since time immemorial, and their materialities, especially feather ornaments. The pillar of reflection is the latenira, a feathered helmet that encapsulates a “multicollectivity” of Iny knowledge. By monitoring the making of this artifact and ethnographic records of its use in ritual contexts, it was possible to penetrate part of this “multicollectivity” of knowledge: “craftsmanship” and the artisans’ technical processes; the relationship between the Iny and the birdlife of the Araguaia River; the meaning of feathers in ancient stories from mythical time; and, finally, the process of constructing male identity through headdresses and the interaction between the different Iny cosmological levels.